Genetic algorithms in engineering systems - Zalzala, A. M. S. (Ali M. S.); Fleming, P. J. (Peter J.) (Institution of Electrical Engineers, 1997)
The book reviews developments in the following fields: multiobjective genetic algorithms; scaleable neural architecture evolution; chaotic systems identification; job shop scheduling; evolutionary algorithms; aerodynamic inverse optimisation problems; and VLSI layout genetic design.